1996
DOI: 10.1165/ajrcmb.15.5.8918368
|View full text |Cite
|
Sign up to set email alerts
|

Postpneumonectomy lung growth: a model of reinitiation of tropoelastin and type I collagen production in a normal pattern in adult rat lung.

Abstract: Elastic and collagen fibers confer recoil and tensile strength on the pulmonary vasculature, airways, alveolar walls, and pleura. These durable extracellular matrix components are primarily synthesized during lung development and growth, and are expressed at very low levels in healthy adult lung. However, reinitiation of elastin and collagen synthesis in diseases of adult lung, such as idiopathic pulmonary fibrosis, often leads to excessive or aberrant deposition of elastin and collagen which contribute to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 0 publications
1
22
2
Order By: Relevance
“…This is in accord with in situ hybridisation data, which demonstrated tropoelastin and procollagen-I mRNA expression to be uniformly distributed throughout the gas exchange area of rat lungs 3, 7 and 14 days after PNX [37]. Studies in young and adult dogs undergoing right lung PNX revealed that growth of alveolar septa is characterised by an initial disproportionate increase in interstitial cells and matrix by nearly 3.6-fold, whereas epithelial and endothelial cells increase ,2-fold compared with control lungs [14,38].…”
Section: Discussionsupporting
confidence: 90%
“…This is in accord with in situ hybridisation data, which demonstrated tropoelastin and procollagen-I mRNA expression to be uniformly distributed throughout the gas exchange area of rat lungs 3, 7 and 14 days after PNX [37]. Studies in young and adult dogs undergoing right lung PNX revealed that growth of alveolar septa is characterised by an initial disproportionate increase in interstitial cells and matrix by nearly 3.6-fold, whereas epithelial and endothelial cells increase ,2-fold compared with control lungs [14,38].…”
Section: Discussionsupporting
confidence: 90%
“…ELN, which provides important structural properties to the lung, is upregulated by mechanical ventilation in premature neonatal lambs (59), baboons (56,59), and mice (11). ELN is normally expressed in the lung during development and is quiescent in healthy adult lung (52), but aberrant ELN expression is induced in fibrotic disorders of the lung (72), in pulmonary hypertension (78), and during lung growth in response to pneumonectomy (47). GPC3, which has not been previously associated with VILI, was repressed in our samples and is repressed by TGF-␤ (66).…”
Section: Discussionmentioning
confidence: 99%
“…Because elastin and collagen have been shown to play an integral part in the development of alveoli [19, 20, 21]as well as in the growth of the residual lung after lobectomy [22], we examined the lungs for evidence of resynthesis of these connective tissue elements in the presence or absence of ATRA treatment. As previously reported in hamsters [23], elastase administration to mice was followed by elastin mRNA expression in the alveolar walls, as seen by in situ hybridization (fig.…”
Section: Discussionmentioning
confidence: 99%